BE: Inspired in FBE - Atta Idrawani, Zaini; Abdul Wafi, Razali; Nurakmal, Abdullah Goh (YouTube, 2020)
A 30 seconds promotional video of the Faculty of Built Environment UNIMAS. Fakulti Alam Bina UNIMAS